(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2023)
Goji berry (Lycium barbarum L.) is described as a food with several health benefits. This valuable fruit has been processed into fruit leather, which is one of the important traditional products. This study allowed us to determine the effect of changing formulations (starch and flour) and cooking times (10, 15, and 20 min) on quality criteria during goji berry leather production. The goji berry leather samples exhibited the following characteristics: pH values ranging from 4.96 to 4.99, titration acidity values spanning from 2.97% to 3.23%, dry matter content within the range of 84.78% to 87.69%, ash content between 3.12%, and 4.27%, water activity (aw) values ranging from 0.37 to 0.38, protein content between 14.71%, and 15.66%, HMF content varying from 17.33 mg/kg to 34.51 mg/kg, total phenolic content ranging from 7.14 mg GAE/g to 7.89 mg GAE/g, total sugar content falling between 61.18%, and 63.89%, reducing sugar content within the range of 60.13% to 61.89%, sucrose content ranging from 0.91% to 2.25%, thickness values ranging from 0.74 mm to 0.89 mm, hardness values varying between 17.09, and 33.27, stickiness values within the range of 4.10 to 23.34, cohesiveness values from 0.85 to 1.00, elasticity values ranging from 0.88 to 0.97, chewability values spanning from 12.85 to 30.85, L* values ranging from 27.27 to 32.66, a* values between 8.62, and 10.32, b*values varying from 7.06 to 8.59, C* values within the range of 11.15 to 12.81, and H° values falling between 39.31, and 41.13. Following the sensory evaluation of leather samples, it was determined that the color score ranged from 3.80 to 4.27, the smell score fell between 3.53 and 4.00, the taste score varied from 2.93 to 4.00, the mouthfeel score ranged from 2.93 to 3.93, and the general acceptability score was found to be within the range of 3.27 to 4.20. It was determined that cooking time and additional additives affect some quality values of the goji berry leather.